EXPLORING JOB STRESS, EMOTIONAL INTELLIGENCE AND JOB INVOLVEMENT IN A SAMPLE OF NIGERIAN AIRFORCE PERSONNEL - L. Nwagbo, Ifeoma; A. Okonkwo, Ejike; I. Obodo, Paul; C. Echezona-Anigbogu, Jovita (African Journal of Social and Behavioural Sciences, 2024)
This cross-sectional study anchored on the theoretical assumption of the integrated theory of job involvement investigated job stress and emotional intelligence as predictors of job involvement in a sample of Nigerian Air Force personnel in Enugu, Nigeria. Two hundred and nine (209) Air Force personnel, comprising 159 males and 50 females between the ages of 19 and 58 years (M=31.13; SD=5.58), participated in the study. They were selected via a two-stage (cluster and purposive) sampling technique. The 15-item job- related tension scale, 14-item emotional intelligence scale, and 20-item job involvement scale were completed by the participants. The results of multiple regression analysis revealed that job stress independently did not predict job involvement; emotional intelligence independently did not predict job involvement; and job stress and emotional intelligence jointly predicted job involvement. Job stress and emotional intelligence accounted for 23% of the variation in the job involvement of Air Force personnel. In view of these findings, this study has recommended that policy makers in the Nigerian Air Force should consider job stress and emotional intelligence to increase job involvement among Air Force personnel.